Undergrads depend on manifestos to vote - New Straits Times, (2012)
The third-year Bachelor of Education student said she would be talking about her manifesto, themed "Your welfare, my responsibility". Wong was also pushing for better facilities for the disabled, especially in residential colleges and food courts.